Niitooii—"The Same That Is Real": Parallel Practice, Museums, and the Repatriation of Piikani Customary Authority - Noble, Brian (Anthropologica, 2022)
Over the last two decades, use of museum-repatriated ceremonial Bundles and associated knowledges, practices, songs and rights by Piikani people has also been aiding in the reconstitution of wider socio-economic, political, and authority practices. Related to this, attention is drawn to a specific Piikani Blackfoot trajectory of material-metaphoric action over an extended history of contact relations: that is, of making parallels. A Blackfoot term for this is Niitooii, "the same that is real." As in such Bundle-centred ceremonies as the Sun Dance, Niitooii makes things real because it mobilizes a complex of shadows, transferred rights, and the authority of people and things. Recent Piikani mediation practices parallel this complex against those in Canadian non-native civil and political society which similarly give authority and force to people. In effect, this has helped advance a collateral process of reconstitution: that of reasserting—or repatriating—customary practices of law and governance, which historically have been enacted through the authority of the Bundles themselves.